Antimicrobial activity of reference Lactobacillus strains against WHO priority drug-resistant pathogens through an integrated in vitro and bacteriocin gene clusters analysis - Vidhi Shah; Richa Soni; Milan Dabhi; Dweipayan Goswami; Rushikesh Joshi (The Microbe)
This study examines the antimicrobial properties of probiotic strains against twelve clinically relevant drug-resistant pathogens, including those classified as 'High priority' by the World Health Organization (WHO) for their significant antibiotic resistance. The probiotic strains, Lactobacillus acidophilus (LA, NCDC 13), Lacticaseibacillus casei (LC, NCDC 17), and Lactobacillus plantarum (LP, NCDC 20), were sourced from the National Dairy Research Institute (NDRI) in Karnal, India. Pathogens were isolated from clinical specimens, identified via Matrix-Assisted Laser Desorption Ionization Time-Of-Flight Mass Spectrometry (MALDI-TOF-MS), and their antibiotic resistance profiles characterized using the VITEK® 2 system. The antibacterial effects of the probiotic strains were assessed using agar well diffusion and agar slab methods, demonstrating a spectrum of inhibitory activities against all twelve pathogens. Additionally, in silico genomic analysis was performed to explore the genetic basis of these antibacterial effects. Whole genome sequences of the American Type Culture Collection (ATCC) equivalents for the NDRI strains were traced and obtained from the National Center for Biotechnology Information (NCBI) database, then analyzed using BAGEL-4 to identify bacteriocin gene clusters. This analysis revealed the presence of diverse bacteriocin gene clusters, encoding bacteriocins such as Acidocin, Enterolysin A, Helveticin J, Lactococcin, Sakacin, and Enterocin X, which are known for their antimicrobial properties. These findings provide a genetic basis for the observed in vitro antibacterial activities, highlighting the potential of these Lactobacillus strains to inhibit drug-resistant pathogens. This integrated approach confirms the potential of the NDRI-derived Lactobacillus strains as alternative therapeutic agents against WHO-designated priority pathogens.